Oxygen Uptake, Muscle Activity and Ground Reaction Force during Water Aerobic Exercises - Alberton, C. L.; Pinto, S. S.; Cadore, E. L.; Tartaruga, M. P.; Kanitz, A. C.; Antunes, A. H.; Finatto, P.; Kruel, L. F. M. (International Journal of Sports Medicine, 2014)
This study aimed to compare the oxygen uptake (VO2), the muscle activity of lower limbs, and the vertical ground reaction force (V-GRF) of women performing water aerobic exercises at different intensities. 12 young women performed the experimental protocol, which consisted of 3 water exercises (stationary running [SR], frontal kick [FK] and cross country skiing [CCS]) at 3 intensities (first and second ventilatory thresholds and maximum effort). A two-way repeated measures ANOVA was used. Regarding VO2, different responses between intensities (p<0.001) were found, and values between exercises were similar. For electromyographic activity (EMG), differences between intensities for all muscles (p<0.001) were found. Greater EMG signals were observed in the FK compared to SR for rectus femoris, semitendinosus, vastus lateralis and biceps femoris muscles (p<0.05). Regarding V-GRF, there was an increase in the V-GRF at greater intensities compared to the first ventilatory threshold (p=0.001). In addition, lower values were found during CCS compared to the SR and FK exercises (p<0.001). Thus, greater cardiorespiratory and neuromuscular responses were observed with increasing intensity. Exercises such as CCS could be used to attenuate the V-GRF; if the purpose is to reduce the muscular activity of lower limbs at a specific intensity, SR could be recommended.
Keywords: aquatic exercise; underwater EMG; impact forces